2017
DOI: 10.1037/pspi0000095
|View full text |Cite
|
Sign up to set email alerts
|

Freedom of racist speech: Ego and expressive threats.

Abstract: Do claims of "free speech" provide cover for prejudice? We investigate whether this defense of racist or hate speech serves as a justification for prejudice. In a series of 8 studies (N = 1,624), we found that explicit racial prejudice is a reliable predictor of the "free speech defense" of racist expression. Participants endorsed free speech values for singing racists songs or posting racist comments on social media; people high in prejudice endorsed free speech more than people low in prejudice (meta-analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
92
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(108 citation statements)
references
References 95 publications
(126 reference statements)
8
92
1
Order By: Relevance
“…We predicted a two‐way interaction between race of target (Black or White) and anti‐Black prejudice, replicating past work examining individual differences in anti‐Black prejudice (Roussos & Dovidio, ). Consistent with White and Crandall's () reasoning that that individuals higher in anti‐Black prejudice are more motivated to justify instances of bias against Blacks as protected by free speech principles, we predicted that (as in Roussos & Dovidio, ) higher anti‐Black prejudice would predict more perceived free speech protections in the Black target condition but not in the White target condition. Importantly, beyond the previous research, we further hypothesized that the experimental manipulation designed to enhance the salience of freedom of speech protections would moderate the effects of anti‐Black prejudice and target race.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…We predicted a two‐way interaction between race of target (Black or White) and anti‐Black prejudice, replicating past work examining individual differences in anti‐Black prejudice (Roussos & Dovidio, ). Consistent with White and Crandall's () reasoning that that individuals higher in anti‐Black prejudice are more motivated to justify instances of bias against Blacks as protected by free speech principles, we predicted that (as in Roussos & Dovidio, ) higher anti‐Black prejudice would predict more perceived free speech protections in the Black target condition but not in the White target condition. Importantly, beyond the previous research, we further hypothesized that the experimental manipulation designed to enhance the salience of freedom of speech protections would moderate the effects of anti‐Black prejudice and target race.…”
Section: Introductionsupporting
confidence: 82%
“…In conclusion, the present study builds upon and extends past work on U.S. participants' usage of the right to free speech to justify criminal acts (Roussos & Dovidio, ; White & Crandall, ). It is likely that in a non‐U.S.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In a large-scale study using representative samples of 21 European countries, it was found that when people perceive realistic and symbolic threats to the ingroup, they find it acceptable and justified to express opposition to immigration (Pereira et al, 2010). Similarly, in a series of eight studies, White and Crandall (2017) demonstrated that prejudiced people use the principle of free speech to justify someone else's anti-Black behavior. Together, these different lines of research indicate that a motive for justification makes people look for (ideological) beliefs that legitimize their group-based antipathy and its expression in negative outgroup behavior.…”
Section: Prejudice and Justificationmentioning
confidence: 99%